Luther and the Sacramentality of Penance - Bagchi, David (Studies in church history, 2004)
At the beginning of his De captivitate Babylonica ecclesiae praeludium of early October 1520, Luther announced that there, were not seven sacraments of the Church, but only three - baptism, penance, and the Lord’s Supper. By the end of the treatise, the three had been reduced to two. His reasoning was starkly logical. A sacrament, to be a sacrament, must contain the promise of forgiveness of sins, and have attached to it a visible sign instituted by Jesus Christ. Because no such visible sign is associated with the rite, penance cannot be a sacrament. A reasonable inference to draw is that Luther must have come to reject the sacramentality of penance by the time he composed De captivitate Babylonica, in perhaps August 1520.